“Innovative” family cattle ranchers: recognizing facets of livestock in the Campanha Gaúcha - Langbecker, Tatielle Belem; Arbage, Alessandro Porporatti; Viana, João Garibaldi Almeida (Science & Technology Journals, 2024)
The objective of this article was to characterize the socioeconomic profile of family cattle ranchers from the Campanha Gaúcha region, in Brazil, who are engaged in innovative processes, and to analyze changes in the routines of activities in family cattle production units. For that, a study of multiple cases was developed in Alegrete and Santana do Livramento, in the Campanha Gaúcha region. As family livestock has been distanced from innovative processes and changes, it was necessary, at a first moment, to bring it closer and recognize the research participants as family livestock farmers. Part of the effort also makes it possible to review, or expand, the understanding of innovative processes, which can be identified in reports on changes in routines, trajectories, and experiences of the participants. Therefore, a little-discussed facet of family livestock is recognized: the innovative family livestock farmers. A space is then opened for new discussions that consider the dynamics and contexts of social categories as starting points for analyses and understanding of demands of these farmers.